2005
DOI: 10.1111/j.1399-6576.2005.00869.x
|View full text |Cite
|
Sign up to set email alerts
|

Local anesthesia for functional endoscopic sinus surgery employing small volumes of epinephrine‐containing solutions of lidocaine produces profound hypotension

Abstract: Local infiltration of low-dose epinephrine causes temporary significant hemodynamic changes particularly a marked decrease in BP during FESS under general anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
40
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 16 publications
1
40
0
Order By: Relevance
“…Thus, the transnasal local anesthetic infiltration may cause systemic absorption of the local anesthetics, and thereby analgesic effects [12]. Besides, the combined effect of local anesthetics and general anesthesia in inducing hypotension may minimize the risk of surgical complications and stabilize hemodynamics [2]. In our study, the decrease in HR in the block groups is obviously reported; however, MAP remained high in bupivacaine group after the operation.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Thus, the transnasal local anesthetic infiltration may cause systemic absorption of the local anesthetics, and thereby analgesic effects [12]. Besides, the combined effect of local anesthetics and general anesthesia in inducing hypotension may minimize the risk of surgical complications and stabilize hemodynamics [2]. In our study, the decrease in HR in the block groups is obviously reported; however, MAP remained high in bupivacaine group after the operation.…”
Section: Discussionmentioning
confidence: 78%
“…However, it is associated with complications such as bleeding and postoperative pain [2]. It is stated frequently that the combination of a peripheral nerve block with general anesthesia (GA) may be effective to limit these drawbacks [3].…”
Section: Introductionmentioning
confidence: 99%
“…Skin, mucosa, as well as kidney arterioles display vasoconstriction on account of a-receptor predominant activation. Low concentrations of adrenaline lead to preferential b2 receptor activation leading to vasodilatation in bronchiolar smooth muscle while increased ranges activate a-receptor-mediated vasoconstriction in vascular smooth muscle [5]. Infiltration of low-dose adrenaline leads to short-term significant hemodynamic alterations, decrease in blood pressure with a slightly increased heart rate during nasal surgery under general anesthesia [6].…”
Section: Discussionmentioning
confidence: 99%
“…10,[12][13][14][15] Although these effects are of significant concern, they are largely the result of intravascular injection and there is limited literature on the safety of topical CE use or the optimal dose. 11,[16][17][18][19] One study concluded that topical CE use was safe in sinus surgery when combined with avoidance in patients with comorbid cardiac disease. 20 An additional practical concern with the use of CE arises from the potential for the masking of arterial bleeding, which may manifest postoperatively after the vasoconstriction has resolved.…”
mentioning
confidence: 98%